Veiled Superheroes - Sarah Shapley (International Institute of Islamic Thought, 2018)
Sophia Rose Arjana’s book Veiled Superheroes: Islam, Feminism, and Popular Culture raises a timely and critical discussion. The interdisciplinary nature of the book provides insight into various subjects, including women’s studies, theology, and popular culture. Arjana, with Kim Fox, focuses on Muslim female (Muslima) superheroes. In a world where so often women (and in particular, Muslim women) are politicized, Arjana offers an alternate exploration of how Muslima superheroes are poised to battle both Western and Islamic misogyny. Chapter 1, “Muslim Women in Popular Culture,” gives an overview of the discourse around Muslim women. The chapter explores how Orientalism has influenced the presentation of Muslim women, particularly noting how Muslim women lose agency in all discussions. Arjana looks specifically at how the comic and cartoons have been subject to this thinking. She addresses how Muslims fall into the villain or the rescue narrative and then turns to the problematic representation of some Muslima superheroes. Comics are just the starting point, for such representations are found in cartoons and film as well. While this chapter provides a great basis for the rest of the book and an essential introduction to the narrative that has often surrounded Muslim women, it does at times jump quickly from one discussion to the next (as continues through much of the book) ...